Institutional Factor of Sustainable Development of the Countries in Eastern Europe: Methodological Aspect - G. Medvedev, Valentin; A. Lukina, Sardaana; V. Strelnikov, Evgeniy; Thanh Nguyen, Phong; Hoang Thuy To Nguyen, Quyen Le (International Journal of Psychosocial Rehabilitation, 2024)
The formation of a new system of political relations in Eastern Europe has a number of features that are insufficient to determine the qualities of the previous era. The study of the positive and negative experience of democratic transit and the subsequent consolidation of democracy in the countries of the region is of interest from the point of view of developing new approaches to the study of transition problems. The study of national models of transition to democracy raises a very important question about the adequacy of the choice of ways to consolidate democracy. Realization of sustainable development goals is a spatially differentiated and cyclical process. In some countries, the movement towards sustainability is faster than in others. Many developed and developing countries have adopted sustainable development policies, ratified international treaties, and made commitments. In others, the concept of “sustainable development” is an abstraction that is remote from the real life of people. A special place in the implementation of sustainable development strategies is held by the countries of Eastern Europe. The article touches upon modern problems of the development of territorial systems. The necessity of the transition from the paradigm of "instability" to the concept of sustainable development is shown. The main provisions of the integral concept of sustainable development and its significance for the future evolution of territories are characterized. The main factors and causes of global environmental, economic and social instability are analyzed. The features of the implementation of the concept of sustainability in the countries of Eastern Europe are characterized.